Search for new physics in final states with a single photon and missing transverse momentum in proton-proton collisions at √s=13 TeV; Journal of High Energy Physics; Vol. 2019, iss. 2 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen